Accounting and Finance: An Introduction - McLaney, Eddie; Atrill, Peter (Harlow : Pearson, 2020)
The same book as 'Accounting: An Introduction', but now with a new title to truly reflect its broad coverage. This comprehensive guide covers financial accounting, management accounting and financial management in a single text, and provides the background and tools to make informed, successful business decisions.
Keywords: Accounting